2019
DOI: 10.14218/jcth.2019.00036
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholangiocarcinoma and Thermal Ablation: Long-term Results of An Italian Retrospective Multicenter Study

Abstract: Background and Aims: Despite resection being considered the treatment of choice for intrahepatic cholangiocarcinoma (ICC), percutaneous thermal ablation can be an alternative treatment for patients unfit for surgery. Our aim was to compare long-term results of percutaneous sonographically-guided radiofrequency ablation (RFA) with highpowered microwave ablation (MWSA) in treatment of ICC. Methods: Results of 71 ICC patients with 98 nodules treated with RFA (36 patients) or MWSA (35 patients) between January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…A larger, multicenter study was done in Italy, also comparing the two techniques. In total, 71 patients were treated, including 36 with RFA and 35 with MWA [29]. They concluded that patients treated with MWA for ICCA nodules <3 cm survived longer than patients treated with RFA (p < 0.005).…”
Section: Rfa Vs Mwamentioning
confidence: 99%
“…A larger, multicenter study was done in Italy, also comparing the two techniques. In total, 71 patients were treated, including 36 with RFA and 35 with MWA [29]. They concluded that patients treated with MWA for ICCA nodules <3 cm survived longer than patients treated with RFA (p < 0.005).…”
Section: Rfa Vs Mwamentioning
confidence: 99%
“…In particular, thermal ablation may not be indicated in case of relevant extrahepatic disease, class C Child-Pugh, major invasion of bile duct or vessel invasion or in case haemorrhagic diathesis or decompensated liver. While HCC has been traditionally the only primary hepatic malignancy to be treated percutaneously, more reports are now available for the treatment of non-resectable primary or recurrent cholangiocarcinoma [29]. A recent meta-analysis on the topic reported a pooled 1, 3, and 5-overall survival (OS) rates of 76% (95% confidence interval [CI]: 68–83%), 33% (21–44%) and 16% (7–26%) [30].…”
Section: Advances In Liver Imaging and Guidancementioning
confidence: 99%
“…Some studies have shown that precoagulatedassisted LR can lead to severe postoperative complications, such as abdominal abscesses, bile fistula, and bile duct damage [10]. Some studies have also shown that MW-assisted LR (MW-LR) or RF-assisted LR (RF-LR) enables minimum blood loss and improves resection margins [11,12]. Therefore, in theory, this procedure may be beneficial for the survival of patients with HCC.…”
Section: Introductionmentioning
confidence: 99%